Comparison of the penetration of three endodontic sealers into dentinal tubules with scanning electron microscopy - Vega-Yslachin, Margarita (2024)
Objective: To compare in vitro, through the use of a scanning electron microscope, the penetration of three endodontics sealers: Based on epoxy resin AH Plus®, based on polydimethylsiloxane Roekoseal® and based on Calcium Hydroxide, Apexit Plus® in the dentinal tubules 3 and 7mm from the root apex with the lateral compaction technique in single-root inferior premolar pieces. Materials and Methods: In vitro study, 36 teeth were prepared and divided into three groups of 12 pieces each group. All the pieces were prepared and each group was filled with three different endodontic sealers. Subsequently, the pieces were cut transversely at 3 and 7 mm from the root apex; They were then prepared to be taken to the scanning electron microscope to observe the penetration of the sealers into the dentinal tubules. Results: The Anova test was used to compare the three groups and the Student's T test was used to evaluate the penetration of each of the sealers at 3 and 7 mm. The Post Hoc Tukey test was also performed to evaluate between the sealers groups. When comparing the three groups of endodontic sealers, greater penetration was found with the Roekoseal® sealer at 3mm with a statistically significant difference in the Anova test (p=0.04). When comparing each of the sealers at 3mm and 7mm, only significant differences were found (p=0.04) in AH Plus® showing better penetration at 7 mm compared to 3mm and when it was compared between the groups of sealers at both 3 and 7 mm there were no statistically significant differences. Conclusions: The three sealers tested penetrated the dentinal tubules. At 3 mm, Roekoseal® sealant outperformed the other two sealants, and at 7 mm, there was no significant difference between them.